2009
DOI: 10.5694/j.1326-5377.2009.tb02590.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of point‐of‐care testing for therapeutic control of chronic conditions: results from the PoCT in General Practice Trial

Abstract: Objective: To compare the clinical effectiveness of point‐of‐care testing (PoCT) and that of pathology laboratory testing, as measured by therapeutic control in chronic conditions. Design: Multicentre, cluster randomised controlled trial using non‐inferiority analysis. Setting: 53 Australian general practices in urban, rural and remote areas across three Australian states, September 2005 to February 2007. Participants: 4968 patients with established type 1 or type 2 diabetes, established hyperlipidaemia, or ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 5 publications
1
51
1
Order By: Relevance
“…Various POC devices are in common use in the community in Australia and Europe 9. As with other studies, discrepancies in readings were more likely out of the therapeutic ranges, especially when supratherapeutic 10–13.…”
Section: Discussionsupporting
confidence: 50%
“…Various POC devices are in common use in the community in Australia and Europe 9. As with other studies, discrepancies in readings were more likely out of the therapeutic ranges, especially when supratherapeutic 10–13.…”
Section: Discussionsupporting
confidence: 50%
“…Only one trial found the influence of POC testing on glycaemic control to be the same or better than laboratory testing,[38] was associated with same or better medication adherence[37] increased patient satisfaction in general practice[39] significant cost savings to patients and families[40], but cost-effectiveness was uncertain. [40] The latter outcome is pertinent to our study.…”
Section: Discussionmentioning
confidence: 99%
“…This may have resulted from improved management of patients when PoCT is used as demonstrated in our Trial [9], which may in turn have resulted in reduced hospital visits for patients with diabetes or on anticoagulant therapy. In contrast, hospital admission costs increased for the lipids PoCT group, but again were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The intermediate outcome indicator used in the cost-effectiveness analysis was the proportion of patients within the therapeutic range for each condition at the end of the Trial [6,9]. The point estimates and confidence intervals for the health outcome indicators are presented in Bubner et al [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation